Teachers’ Oral Feedback in EFL Classroom Interaction (A Descriptive Study of Senior High School in Indonesia) - Erfiani Irawan; Kisman Salija (ELT Worldwide: Journal of English Language Teaching, 2017)
This research aimed to identify types and ways of oral feedback used by teachers in EFL classroom interaction based on the theory of Tunstall & Gipss (1996), Lyster & Ranta (1997), Cullen (2002), and Mackiewicz & Thompson (2013). This research also investigated teachers’ reasons for using oral feedback and students’ perceptions of oral feedback used by teachers in EFL classroom interaction. This research was conducted at Senior high school in Indonesia. The researcher applied descriptive qualitative research method. The subjects of this research were 2 English teachers and 12 students. All of them were chosen by using purposive sampling technique. The instruments of this research were audio recording, field notes, and interview. The result of this research showed that the teachers used 5 types of oral feedback, namely evaluative feedback, corrective feedback, descriptive feedback, interactional feedback, and motivational feedback. The teachers used oral feedback through providing evaluative statements to students’ work or performance, indicating and correcting students’ errors explicitly or implicitly, informing students’ achievement and the improvement strategies of learning, clarifying and embellishing some ideas on students’ responses, and providing motivational statements to students. The teachers employed oral feedback because of teachers’ responsibility and obligation to provide it, the effective and efficient feedback mode, the utility of oral feedback, positive effect to students, and consequences of none of oral feedback. Mostly, the students perceived positively to oral feedback. Some students found felt sensitive to oral feedback. Nevertheless, they still realized to its positive effect on the result of their work or performance.